A phase III, open-label clinical trial evaluating pegunigalsidase alfa administered every 4 weeks in adults with Fabry disease previously treated with other enzyme replacement therapies - Holida, Myrl; Linhart, Aleš; Pisani, Antonio; Longo, Nicola; Eyskens, François; Goker-Alpan, Ozlem; Wallace, Eric; Deegan, Patrick; Tøndel, Camilla; Feldt-Rasmussen, Ulla; Hughes, Derralynn; Sakov, Anat; et al. (Journal of inherited metabolic disease, 2025)
Pegunigalsidase alfa, a PEGylated α-galactosidase A enzyme replacement therapy (ERT) for Fabry disease, has a longer plasma half-life than other ERTs administered intravenously every 2 weeks (E2W). BRIGHT (NCT03180840) was a phase III, open-label study in adults with Fabry disease, previously treated with agalsidase alfa or beta E2W for ≥3 years, who switched to 2 mg/kg pegunigalsidase alfa every 4 weeks (E4W) for 52 weeks. Primary objective assessed safety, including number of treatment-emergent adverse events (TEAEs). Thirty patients were enrolled (24 males); 23 previously received agalsidase beta. Pegunigalsidase alfa plasma concentrations remained above the lower limit of quantification throughout the 4-week dosing interval. Thirty-three of 182 TEAEs (in 9 patients) were considered treatment-related; all were mild/moderate. No patients developed de novo anti-drug antibodies (ADAs). In the efficacy analysis (n = 29), median (inter-quartile range) eGFR change from baseline over 52 weeks was -1.9 (-5.9; 1.8) mL/min/1.73 m2 (n = 28; males [n = 22]: -2.4 [-5.2; 3.2]; females [n = 6]: -0.7 [-9.2; 2.0]). Overall, median eGFR slope was -1.9 (-8.3; 1.9) mL/min/1.73 m2/year (ADA-negative [n = 20]: -1.2 [-6.4; 2.6]; ADA-positive [n = 9]: -8.4 [-11.6; -1.0]). Lyso-Gb3 concentrations were low and stable in females, with a slight increase in males (9/24 ADA-positive). The BRIGHT study results suggest that 2 mg/kg pegunigalsidase alfa E4W is tolerated well in stable adult patients with Fabry disease. Due to the low number of patients in this study, more research is needed to demonstrate the effects of pegunigalsidase alfa given E4W. Further evidence, outside of this clinical trial, should be factored in for physicians to prolong the biweekly ERT intervals to E4W. TAKE-HOME MESSAGE: Treatment with 2 mg/kg pegunigalsidase alfa every 4 weeks could offer a new treatment option for patients with Fabry disease.
Keywords: výsledek terapie; Young Adult; Fabry Disease; lyso‐Gb3; Recombinant Proteins; polyethylenglykoly; Male; Fabry disease; Sphingolipids; alpha-Galactosidase; mladý dospělý; Drug Administration Schedule; eGFR; Fabryho nemoc; pegunigalsidase alfa; Adult; trihexosylceramidy; Aged; dospělí; mužské pohlaví; senioři; Trihexosylceramides; Treatment Outcome; rekombinantní proteiny; lysosomal storage disorders; sfingolipidy; Polyethylene Glycols; lidé; ženské pohlaví; Humans; enzymová substituční terapie; enzyme replacement therapy; rozvrh dávkování léků; alfa-galaktosidasa; Female; lidé středního věku; Enzyme Replacement Therapy; Middle Aged